Luminescent sensing and photocatalytic degradation properties of an uncommon (4, 5, 5)-connected 3D MOF based on 3, 5-di(3′, 5′-dicarboxylphenyl)benzoic acid. Issue 30 (12th July 2017) - Jin, Jun-Cheng; Wu, Xi-Ren; Luo, Zhi-Dong; Deng, Fang-Yuan; Liu, Jian-Qiang; Singh, Amita; Kumar, Abhinav
Abstract : An uncommon microporous MOF1 used as fluorescent chemosensor for NACs and as photocatalyst. Abstract : An uncommon microporous metal–organic framework (MOF), {[Zn5 (L)2 (DMF)2 (μ3 -H2 O)]·2DMF} (1 ), was successfully constructed using a less exploited symmetrical pentacarboxylate ligand, 3, 5-di(3′, 5′-dicarboxylphenyl)benzoic acid (H5 L). The MOF1 features a trinodal (4, 5, 5)-connected topology having a Schläfli symbol of (4 2 ·6 3 ·8)(4 5 ·6 5 )2 (4 6 ·6 4 ) and is stable in air as well as in acidic/basic aqueous media at room temperature. The MOF1 behaves as a luminescent sensor for the highly selective and sensitive detection of Fe 3+, Fe 2+, Cu 2+ and Ag + ions and o -nitrophenol (MNP), p -nitrophenol (PNP), 2, 4-dinitrophenol (DNP), 2, 4, 6-trinitrophenol (TNP) and 4-nitrotoluene (4-NT). Furthermore, the photocatalytic properties of1 for the degradation of Methyl violet (MV) and Rhodamine B (RhB) have been explored. The possible quenching of the emissions of1 in the presence of nitroaromatics has been addressed by theoretical calculations and the photocatalytic activity of1 against organic dyes has been addressed using density of states (DOS) calculations.